Problems experienced by educators in planning social sciences lessons and using them as tools to achieve the learning outcomes in the senior phase level in the Mankweng Circuit of Education - Kgopa, Makoeea Salome (My University, 2006)
South Africa chose an Outcomes-Based Education approach to underpin the new education system called Curriculum 2005, which was later reviewed to become the Revised National Curriculum Statement. This became policy and it was delivered to schools for educators to apply in their learning programmes work schedules and lesson plans. This study focuses on the lesson plan as a tool to be used by individual educators. Although the other curriculum development steps cannot be ignored, the empirical study of this investigation will be on lesson planning. The empirical study investigates the problems experienced by educators in planning Social Sciences lessons and uses them as tools to achieve the learning outcomes at senior Phase level. In order to find possible solutions to problems experienced by educators in the Department of Education, the following questions were constructed for investigation: • What is the structure of a lesson plan in the Social Sciences learning area? • How have educators changed their ways of planning lessons from the old to the new system? • What are the problems experienced by educators in the planning and use of Social Sciences lessons? The above questions guided this study to yield the following results: • The majority of educators does not know and understand how to plan by using learning outcomes in the lesson plan structure. It is not only with learning outcomes but even the use of other elements of a lesson plan structure makes planning difficult for educators. • Most educators are resistant to change from the old to the new ways of planning lessons. In some cases, educators start by implementing the curriculum without a well written, structured lesson plan because of delays in the delivery of policy documents to schools, workshops which do not address classroom issues but emphasize the design features without relating them to the Social Sciences learning area specifics. ii • The majority of educators experience problems in planning Social Sciences lessons because they were not trained in the revised National Curriculum Statement, because of being in excess. They are not taken for training and are frequently not enthusiastic to implement what they have learnt from Outcomes- Based Education workshops in the classroom because they fear failure due to a lack of managerial intervention for support, guidance and follow-ups. The recommendations of this study were guided by the findings of the empirical results.
Thesis (M.ED.) --University of Limpopo, 2006
Keywords: Outcome-based-educaton; Curriculum 2005